Factors of Successful Implementation of Inclusive Physical Education Programs in Senior High Schools - Suhandrianto, Suhandrianto; Wardiah, Dessy; Lanos, Muhsana El Cintami (PPSDP International Journal of Education, 2024)
This research aims to analyze the factors that influence the successful implementation of the inclusive physical education program at SMAN 2 Waytenong. Using a qualitative approach and case study method, data were collected through in-depth interviews with teachers, students and administrative staff, as well as direct observation. Data analysis was carried out using the thematic analysis method to identify the main influencing factors. The research results show that school management support, teacher readiness and competence, parent participation and support, availability of facilities and infrastructure, student attitudes and perceptions, as well as curriculum and learning materials are key factors that influence the success of the program. This research concludes that supportive management, teacher training, parental involvement, adequate facilities, positive student attitudes, and an inclusive curriculum are essential for effective implementation. The proposed recommendations include improving teacher training, providing better resources, outreach to parents, developing an inclusive curriculum, and creating a friendly and supportive school environment. By managing these factors, it is hoped that the inclusive physical education program at SMAN 2 Waytenong can be successful and provide maximum benefits for all students.